SLC38A2 Overexpression Induces a Cancer‐like Metabolic Profile and Cooperates with SLC1A5 in Pan‐cancer Prognosis - Huang, Meng‐Sen; Chang, Jen‐Hsuan; Lin, Wen‐Ching; Cheng, Yu‐Hsiang; Li, Fu‐An; Suen, Ching‐Shu; Hwang, Ming‐Jing; Chang, Chung‐ke; Mou, Kurt Yun (Chemistry, an Asian journal, 2020)
Cancer cells have dramatically increased demands for energy as well as biosynthetic precursors to fuel their restless growth. Enhanced glutaminolysis is a hallmark of cancer metabolism which fulfills these needs. Two glutamine transporters, SLC1A5 and SLC38A2, have been previously reported to promote glutaminolysis in cancer with controversial perspectives. In this study, we harnessed the proximity labeling reaction to map the protein interactome using mass spectrometry‐based proteomics and discovered a potential protein‐protein interaction between SLC1A5 and SLC38A2. The SLC1A5/SLC38A2 interaction was further confirmed by bimolecular fluorescence complementation assay. We further investigated the metabolic influence of SLC1A5 and SLC38A2 overexpression in human cells, respectively, and found that only SLC38A2, but not SLC1A5, resulted in a cancer‐like metabolic profile, where the intracellular concentrations of essential amino acids and lactate were significantly increased as quantified by nuclear magnetic resonance spectroscopy. Finally, we analyzed the 5‐year survival rates in a large pan‐cancer cohort and found that the SLC1A5hi/SLC38A2lo group did not relate to a poor survival rate, whereas the SLC1A5lo/SLC38A2hi group significantly aggravated the lethality. Intriguingly, the SLC1A5hi/SLC38A2hi group resulted in an even worse prognosis, suggesting a cooperative effect between SLC1A5 and SCL38A2. Our data suggest that SLC38A2 plays a dominant role in reprogramming the cancer‐like metabolism and promoting the cancer progression, whereas SLC1A5 may augment this effect when co‐overexpressed with SLC38A2. We propose a model to explain the relationship between SLC1A5, SLC38A2 and SCL7A5, and discuss their impact on glutaminolysis and mTOR signaling. We employed proximity‐labeling proteomics to discover a protein‐protein interaction between SLC1A5 and SLC38A2, two glutamine transporters that were previously implicated in the enhanced glutaminolysis of cancer cells. Our nuclear magnetic resonance experiments and the clinical data analysis suggest that SLC38A2 plays a dominant role in reprogramming the cancer‐like metabolism and promoting the cancer progression, whereas SLC1A5 may augment this effect when co‐overexpressed with SLC38A2.